La importancia del guiñol dentro del mundo lorquiano - Katona, Eszter (Acta Hispanica, 2012)
Federico García Lorca was a versatile artist, known as a musiáan, poet, dramatist, essaywriter, and the director and actor of the Barraca Troupe, to mention only some important moments of his short but outstanding artistic career. Since his poems and dramas are well known amongst the Hungarian audience, instead of repeating clichés, this study selected a segment of Lorca's life work that is still considered a foster child among literary genres. This genre is the puppet-theatre, which always played a significant role in Lorca's life. The roots of this enthusiasm must be sought in his childhood, while as an adult ljorca consciously tried to search and pass on his knowledge of the tradition ofpuppet-shows and also lullabies. With the revival of such folk-rooted, andent cultural treasures, the Andalusian artist wanted to guide his audience back to childhood innocence untouched by riviligation. Avant-garde movements from the beginning of the century were also familiar with the genre of puppet-theatre. Several Spanish litterateurs (Jarinto Benavente, Valle In clan, Rafael Alberti, Jacinto Grau) wrote plays especially for puppets, mostly —and surprisingly differing from our contemporary perception of puppet shows— for adult audiences. Lorca's life work includes four surviving works written for puppet-theatre (Cristobícal, Ta tragicomedia de Don Cristóbal y la seña Rosita, La niña que riega la albahacay el príncipe preguntón, Retablillo de Don Cristóbal), this study willfocus on presenting these plays.